Reconstruction of the Constitutional Court's Authority from a Negative Legislator to a Positive Legislator for the Sake of Substantive Justice - Selviana Teras Widy Rahayu; Boy Nurdin (Ridwan Institute, 2026)
The Constitutional Court of Indonesia, initially established as a negative legislator following Hans Kelsen’s doctrine, possesses the authority to annul laws that contradict the 1945 Constitution. Over the past two decades, strict adherence to this model has revealed critical limitations, as annulment of statutory norms often generates legal vacuums, uncertainty, and potential infringement on citizens’ constitutional rights. This study addresses the evolving role of the Constitutional Court as a positive legislator to ensure substantive justice, particularly when legislative delays hinder the enforcement of citizens’ rights. The research aims to analyze the legal, philosophical, and sociological foundations underpinning this transformation and evaluate the mechanisms through which the Court addresses legal deadlocks. Employing normative legal research, the study examined secondary data from statutory laws, Constitutional Court decisions, legal literature, and scholarly analyses. Data were collected through systematic library research and document review, and analyzed qualitatively using descriptive, interpretative, and conceptual techniques. Findings indicate that the Court’s conditional constitutional and unconstitutional rulings enable the formulation of transitional norms, preventing legal chaos while safeguarding substantive justice. The reconstruction of the Court’s authority allows it to act as an emergency legislator, filling normative gaps without supplanting legislative power. This approach ensures citizens’ constitutional rights are effectively protected, demonstrating a balance between judicial activism and the principles of separation of powers.